Understanding landowner preferences for traditional and nature-based solutions incentive programs in North Carolina, USA - Courtney B. Deviney; Rajan Parajuli; Frederick W. Cubbage; Erin O. Sills; Robert E. Bardon (PLoS ONE, 2026)
Financial incentive programs, commonly administered by public institutions, have long supported sustainable land management practices in the United States, including soil conservation, water quality improvement, and biodiversity preservation. Recently, these initiatives have expanded under the concept of nature-based solutions (NBS), which emphasize land-based practices that deliver co-benefits for people and ecosystems. However, the effectiveness of such programs often depends on how well they align with landowners’ diverse values, preferences, and motivations. This study examines factors influencing forest and farm landowners’ likelihood of enrolling in traditional and NBS-oriented incentive programs. We surveyed 2,000 forest and farm landowners across four regions in North Carolina to assess how ownership motivations, land use intentions, and personal values influence program participation preferences and compensation expectations. The full information maximum likelihood regression results reveal significant differences between forest and farm landowners in their motivations, future land management plans, and financial expectations. Landowners who reside on their land or have never applied to any cost-share programs before are generally less inclined to participate in either program type. These findings highlight the importance of designing targeted outreach strategies and tailoring program structures to better reflect the values and needs of different landowner groups, thereby improving landowners’ participation and enhancing the long-term effectiveness of land-based conservation and sustainability initiatives.